Efficacy and Safety of Dahuang Zhechong Pill in Silicosis: A Randomized Controlled Trial. (18th November 2021) - Tang, Wu-Yi-Nuo; Liang, Jing-Tao; Wu, Ju; Liu, Li; Lu, Ming-Zhang; He, Xiao-Yan; Wu, Li-Juan; Jiang, Huan-Yu; Wang, Fei; Meng, Xiao; Li, Shun-Pin
Abstract : Background . There is no effective therapy for silicosis, and Dahuang Zhechong pill (DHZCP), an ancient Chinese medicine prescription, may have a therapeutic effect on silicosis. This study aims to verify the efficacy and safety of DHZCP in silicosis. Methods . This is a randomized controlled clinical trial done at Panzhihua Second People's Hospital (Panzhihua City, Sichuan Province, China). Participants diagnosed with silicosis were recruited and randomized to the conventional treatment group (CG) or DHZCP combined with the conventional treatment group (DG). Forced vital capacity % predicted (FVC%), diffusing capacity of the lung for carbon monoxide % predicted (DLCO%), six-minute walk distance (6MWD), peripheral oxygen (SpO2 ), King's Brief Interstitial Lung Disease Questionnaire (K-BILD), and safety outcomes were measured at baseline and 9 weeks. Results . Fifty-six participants (28 in each group) completed the study, and 53 of them (26 in DG and 27 in CG) completed pulmonary function. At 9 weeks, compared with no DHZCP, DHZCP treatment was associated with significant improvements in FVC% (mean ± SD, 95%CI) (8.2 ± 3.9, 0.3 to 16.0), DLCO% (8.6 ± 3.5, 1.5 to 15.7), SpO2 (3.8 ± 0.7, 2.3 to 5.2), and K-BILD total score (6.0 ± 2.3, 1.4 to 10.7). And, there were no statistical differences of safety outcomes between the two groups. Eight patients accepting DHZCP developed mild diarrhea during the first week, which subsequently resolved on its own. Conclusion . DHZCP could improve the pulmonary function, the quality of life, and the exercise capacity of silicosis patients.